The history of a legacy: The MacCormack bibliographic collection in Peru - Valle Rondón, Fernando (2019)
This chronicle shows the circumstances in which Sabine MacCormack’s book collection –donated to the Instituto de Pastoral Andina (IPA) and stored in U. Catolica San Pablo in Arequipa– was inventoried, packed and delivered to Peru. The author –who was in charge of these procedures in South Bend MacCormack’s house– shares his experiences there, his impressions on her relationship to the Andean world and his gratitude to every person who was involved into this valuable project.